Pengaruh Video Edukasi Bullying Terhadap Perkembangan Sosial Anak Usia Dini di PAUD Prima Pertiwi - Rizka Fadhilah Daulay; Mira Yanti Lubis; Hopman Daulay (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
The aim of this research is to determine: (1) the social development of children in PAUD Prima Pertiwi using bullying educational videos, (2) the influence of bullying educational videos on the social development of early childhood in PAUD Prima Pertiwi, Sayur Mahincat village. This research uses a quantitative approach with an experimental type of research. The research design used a one-group pretest-posttest type pre-experiment. The instruments used consisted of observations, interviews and tests. The data analysis technique uses descriptive statistics and carries out conditional tests, namely the normality test and homogeneity test. Test the hypothesis using the "t" test. The results of the research show that: (1) The social development of early childhood in PAUD Prima Pertiwi, Sayur Mahincat village is going well, this can be seen from the results of observations in the pretest and posttest. The pretest obtained an average of 11.9, while the posttest obtained an average of 19.8. From these results, there was a very significant increase from the pretest observation results to the posttest observation results. (2) The results of the "t" test calculation obtained tcount = 7.97 when compared with ttable at a 95% confidence level or 5% error rate with degrees of freedom (db) = N – k = 20 – 2 = 18 obtained ttable 2.10 . If the value of tcount = 7.97 is compared with ttable = 2.106 then it is known that tcount is greater than ttable, (7.97 > 2.106). This means that the proposed hypothesis is accepted as true. This means that there is an influence between bullying educational videos on the social development of early childhood at Prima Pertiwi PAUD Sayur Mahincat village.